Certificateless public key cryptography based provable data possession scheme in edge environment - Ziyuan WANG; Ruizhong DU (Tongxin xuebao)
In the edge environment, data transmission to the cloud needs to pass through a new entity, the edge node, which makes the data security problem more complicated, the confidentiality and integrity of data are difficult to be guaranteed, and the traditional provable data possession scheme is not suitable for the edge environment with a large number of devices.Based on this, a certificateless public key cryptography based provable data possession scheme was proposed for the edge environment, combining the online/offline signature idea, where the user device only needed to perform light computation when uploading data in the case of semi-trusted edge nodes, leaving the rest of the computation to be performed in the offline phase.The scheme used edge nodes for auditing work while supporting auditing in different storage states, as well as privacy protection and other features.The security analysis shows that the proposed scheme is proven to be secure by being able to effectively combat three types of adversary attacks under a stochastic prediction model.Experimental comparisons with other schemes show that the proposed scheme has lowest time overhead.